2017
DOI: 10.3390/md15120373
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Cytotoxic Mechanism of Vibrio parahaemolyticus PirAvp and PirBvp Toxins

Abstract: In aquaculture, shrimp farming is a popular field. The benefits of shrimp farming include a relatively short grow-out time, high sale price, and good cost recovery. However, outbreaks of serious diseases inflict serious losses, and acute hepatopancreatic necrosis disease (AHPND) is an emerging challenge to this industry. In South American white shrimp (Penaeus vannamei) and grass shrimp (Penaeus monodon), this disease has a 70–100% mortality. The pathogenic agent of AHPND is a specific strain of Vibrio parahae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 58 publications
1
62
0
2
Order By: Relevance
“…Furthermore, PirA vp alone did not show activity against any type of erythrocytes tested. Possibly the A subunit participates in stabilizing the complex for a better binding to the possible receptor molecule on the shrimp hepatopancreatic epithelial cells [50]. These results highlight the importance of the interaction between the two subunits of the complex, which could act in molecular synergy to recognize the target molecule, as has been reported for the A and B subunits of the R. communis toxin [51].…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, PirA vp alone did not show activity against any type of erythrocytes tested. Possibly the A subunit participates in stabilizing the complex for a better binding to the possible receptor molecule on the shrimp hepatopancreatic epithelial cells [50]. These results highlight the importance of the interaction between the two subunits of the complex, which could act in molecular synergy to recognize the target molecule, as has been reported for the A and B subunits of the R. communis toxin [51].…”
Section: Discussionsupporting
confidence: 62%
“…To date, the cytotoxic mechanism of PirA/PirB is unclear, although the structures of PirA and PirB are very similar to those of insecticidal Cry toxins produced by Bacillus thuringiensis (Lin, Hsu, & Wang, ), which raises the possibility that their cytotoxic mechanisms are similar. Cry toxin contains three structural domains (domains I, II and III) connected by single linkers (Bravo, Gill, & Soberon, ).…”
Section: Discussionmentioning
confidence: 99%
“…If the role of PirA is similar to that of Cry toxin domain III, then PirA needs to interact with a sugar moiety of a receptor located on the host cell surface to facilitate the binding of domain II to another region in the receptor (Jenkins, Lee, Valaitis, Curtiss, & Dean, 2000). In fact, PirA has a possible sugar-binding pocket (Lin et al, 2017). Binding to this receptor then leads to the activation of domain I to form pores that will eventually cause cell lysis (Lin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatopancreas histopathology shows inflammation and desquamation, while a hemocytic infiltrate is noted. This damage is produced by toxins PirAvp and PirBvp which have a structural similarity to B. thuringiensis Cry pore-forming toxin, so it has been suggested that PirAvp/PirBvp promote a similar process to induce cell death of the hepatopancreas tissue in shrimps [12,13]. Several strategies have been addressed to control diseases that affect a shrimp, such as tank water replacements, good personnel management practices, water monitoring, and use of antibiotics.…”
Section: Introductionmentioning
confidence: 99%